2007
DOI: 10.1002/jcb.21547
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 6 inhibit stress‐induced breast cancer cells apoptosis via both smad and P38 pathways

Abstract: Breast carcinoma is one of the most common malignant tumors and has become a more common cancer in women. BMP6 was abnormally expressed in breast cancer specimens and cell lines. However, the contribution of BMP6 in promoting breast cancer progression remains unknown. The purpose of our study was to establish whether expression of BMP6 in breast cancer cells affect their proliferation or apoptosis and the mechanism. We found that BMP6 inhibited proliferation of MDA-MB-231 cells and blocked cell cycle at G(0)/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…BMP6 neutralization in sera exerted little influence on cell growth (Fig. 9A), implying that BMP6 was not directly involved in regulating cancer cell growth, in agreement with the previous results [49,50]. DFO (at 100 μM) was used as a control to repress cell proliferation (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 91%
“…BMP6 neutralization in sera exerted little influence on cell growth (Fig. 9A), implying that BMP6 was not directly involved in regulating cancer cell growth, in agreement with the previous results [49,50]. DFO (at 100 μM) was used as a control to repress cell proliferation (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 91%
“…This is in agreement with the observation that BMP6 expression develops at the differentiation stage of plasma cells, whereas it is absent in MBCs and only expressed in a small minority of PPC samples. The condition is complicated by the fact that alternative BMP signaling ways through prostanoid generation (Ren et al, 2007) and MAPK (Nohe et al, 2004;Du et al, 2007) have been reported, both pathways being present in MMCs (Hoang et al, 2006;Trojan et al, 2006).…”
Section: Expression Of Bmp6 and Its Receptorsmentioning
confidence: 99%
“…Phosphorylated SMAD1, -5 or -8 proteins form a complex with SMAD4, the only member of the common-partner SMAD proteins, and translocate to the nucleus, where they interact with other transcription factors (Massague, 2000). Alternate BMP signaling pathways include prostanoid generation through cyclooxygenase-2 (Ren et al, 2007) and MAPK (mitogen-activated protein kinase)-dependant activation of p38 or the Ras-and Erk pathway (Nohe et al, 2004;Du et al, 2007). Both pathways have been reported to be present in MMCs (Hoang et al, 2006;Trojan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1A). For example, BMP-2 and BMP-6 inhibit the proliferation of breast cancer cells (2,3). On the other hand, some BMPs may indirectly promote the proliferation of breast cancer cells, such as BMP-4 which has a synergetic effect on the proliferation of breast cancer cells induced by fibroblast growth factor (FGF), epidermal growth factor (EGF) and hepatocyte growth factor (HGF) (4).…”
Section: Bmps and Tumour Biology Of Breast Cancer Cellsmentioning
confidence: 99%
“…In MDA-MB-468, which only expresses Smad-1, BMP-2 fails to induce p21 and inhibits cellular proliferation (9). BMP-6 inhibits proliferation and induces cell cycle arrest at G0/G1 stage in oestrogeninsensitive breast cancer cells (MDA-MB-231) (2).…”
Section: Bmps and Tumour Biology Of Breast Cancer Cellsmentioning
confidence: 99%